Removal of an Azo Dye Congo Red from Aqueous Solution by Electro Coagulation Associated with the In-Situ Adsorption Process - Mohan, S.; Nagabhushana, B. M.; Chikkahanumantharayappa; Shivakumara, C. (Asian Journal of Science and Applied Technology, 2021)
Effective removal of Congo red from the aqueous solution has been studied using the electro coagulation technique using copper wire as both cathode and anode. As the voltage increases from 0.0 V to 55.0 V DC voltage, the removal efficiency increases up to 98% with the time limit of 35 seconds at a normal pH value of 7.0 - 7.85. As the temperature increases from room temperature to 75 0C, the coagulation increases and even the number of pairs of electrodes plays an important role in coagulation. The obtained sludge is characterized to identify its composition.